Interaction of carbon reduction and green energy promotion in a small fossil-fuel importing economy - Rüdiger Pethig; Christian Wittlich (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
We study the incidence of carbon-reduction and green-energy promotion policies in a general equilibrium small open economy that depends on imports of fossil fuels. The focus is on mixed policies that are either price based (emissions taxes and producer price subsidies for green energy) or quantity based (schemes of trading emissions and green certificates). Policy instruments directed head-on toward promoting green energy are shown to also reduce carbon emissions and vice versa but the direct effects are stronger than the side effects, the more so, the greater is the elasticity of substitution in consumption between energy and consumption goods. We calculate the effects of variations in individual policy parameters on all endogenous variables, among them the energy price and the welfare costs. We also determine the impact of exogenous fossil-fuel price shocks on the economy.
Keywords: Q42; Q43; Q48; Q54; 330; carbon reduction; green energy promotion; policy mix; interaction of policies; Klimaschutz; Förderung regenerativer Energien; Policy-Mix; Umweltökonomik; Wirkungsanalyse; Substitutionseffekt; Mineralölpreisschock; Wohlfahrtseffekt; Theorie